ON CLASSIFICATION AND ZONING OF LANDSLIDES IN ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The published and archival materials on the issues related to spreading and appearance of landslides phenomenon in the RA territory have been studied and analyzed in the work. It has been suggested the classification and zoning of the landslides specific to the RA territory should be implemented, referring to the absence of such activities, and taking into account the international experience related to the given phenomenon.
Keywords: natural electric field; micro-crack generation; landslide creation